2022
DOI: 10.3390/antiox11050831
|View full text |Cite
|
Sign up to set email alerts
|

Heracleum persicum Essential Oil Nanoemulsion: A Nanocarrier System for the Delivery of Promising Anticancer and Antioxidant Bioactive Agents

Abstract: Essential oils are important compounds for the prevention and/or treatment of various diseases in which solubility and bio-accessibility can be improved by nanoemulsion systems. Heracleum persicum oil nanoemulsion (HAE-NE) was prepared and biological properties were investigated against human breast cancer cells and normal human fibroblasts foreskin. Particle size, zeta potential and poly dispersity index were 153 nm, −47.9 mV and 0.35, respectively. (E)anethole (57.9%), terpinolene (13.8%), ɣ-terpinene (8.1%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…Also, PDI also reported below 0.2 for majority of produced nanoemulsions which it may be due to application of suitable sonication and high ratio of surfactant to dispersed phase (essential oil) (Table 1). The droplet size of 153 nm and polydispersity of 0.35 also reported by Bashlouei et al [5] for Heracleum persicum essential oil nanoemulsion.…”
Section: Droplet Size and Polydispersity Index (Pdi)supporting
confidence: 79%
See 2 more Smart Citations
“…Also, PDI also reported below 0.2 for majority of produced nanoemulsions which it may be due to application of suitable sonication and high ratio of surfactant to dispersed phase (essential oil) (Table 1). The droplet size of 153 nm and polydispersity of 0.35 also reported by Bashlouei et al [5] for Heracleum persicum essential oil nanoemulsion.…”
Section: Droplet Size and Polydispersity Index (Pdi)supporting
confidence: 79%
“…At the similar attempt, Bashlouei et al [5] concluded that H. Persicum Essential Oil Nanoemulsion could considered as a promising antioxidant and anticancer natural drug in breast cancer therapy. They explained that such antioxidant properties were mainly attributed to (E)-anethole present in H. persicum essential oil.…”
Section: Antioxidant Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, the low oral bioavailability and high volatility of essential oils require ODDS to achieve pharmacological actions in vivo. 8,9 Numerous nanocarriers have been developed to facilitate the oral delivery of essential oils, including various nanoemulsions, 14 Pickering emulsions, 58 inclusion compounds 59 and solid lipid nanoparticles. 60 However, limited studies indicated a comprehensive strategy for encapsulating essential oils in the interior region of nanocarriers without content loss and consolidating the outer layer of nanocarriers to prevent volatilization.…”
Section: Resultsmentioning
confidence: 99%
“…Nanoemulsions exhibit considerable potential for the encapsulation of essential oils, thereby improving the hydrophilicity and stability of essential oils. Essential oils are loaded in the internal oil phase of nanoemulsions, which reduces their volatility and degradation in vitro and in vivo . The emulsifier is the key factor in the preparation of nanoemulsions. Accumulating evidence proved that bovine serum albumin (BSA) is an important emulsifier for preparing nanoemulsions that possess good biocompatibility and biodegradability. , Specifically, BSA can spread on the oil–water interface via reconfiguration.…”
mentioning
confidence: 99%